Recent advances in synergistic effect promoted catalysts for preferential oxidation of carbon monoxide - Jing, Peng; Gong, Xia; Liu, Baocang; Zhang, Jun (Catalysis science & technology, 2020)
Preferential oxidation of CO (PROX) in a H 2 -rich stream is considered as a promising strategy for abatement of trace amounts of CO to prevent poisoning of Pt anodes by H 2 in polymer-electrolyte membrane fuel cells (PEMFCs). The design of efficient catalysts is highly desirable to promote PROX. In this review, the recent advances in noble metal-based and non-noble metal-based catalysts for PROX are reviewed including some representative single-atom catalysts with outstanding catalytic performance. We summarize their synthetic methods, catalytic performance for PROX and reaction mechanisms with special emphasis on the synergistic effects between different components of catalysts that contribute to enhanced catalytic performance. Finally, the remaining challenges in PROX and some related promising strategies are indicated. We reviewed recent advances in catalysts for PROX with emphasis on synergistic effects that contribute to enhanced catalytic performance.